LEADERSHIP, PLANNING, AND CULTURAL VALUES: THEIR IMPACT ON ICT ADOPTION IN ARAB SECTOR HIGH SCHOOLS - Hana Horany, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The Arab society in Israel faces unique challenges stemming from complex socioeconomic realities, educational disparities, and cultural and traditional barriers. These challenges are particularly pronounced among disadvantaged populations, including high schools in the Arab sector in northern Israel and the Bedouin sector in the south. This study examines the impact of management patterns on the implementation of Information and Communication Technologies (ICT) in these contexts, focusing on the interplay between school leadership, teachers, and parents as key drivers of change. The study adopts an integrative approach, involving surveys conducted with 373 high school teachers and 44 semi-structured in-depth interviews—22 with teachers and 22 with parents of students in grades 10–12. Findings highlight the critical role of structured planning, effective communication, monitoring, evaluation, and supervision in the ICT implementation process. Cultural adaptations and strengthened collaboration between parents and teachers emerged as essential factors for success. Furthermore, the study reveals significant gaps in digital literacy among teachers, parents, and students, alongside challenges related to limited access to digital tools and resources. Community-based programs were found to be instrumental in fostering collaboration within the school environment and mitigating cultural and traditional barriers. The study recommends implementing culturally tailored systemic strategies that integrate community collaboration, technological training, and institutional support to enhance ICT integration and reduce educational inequities.